PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PERLENGKAPAN OLAHRAGA REEBOK - Sunny Nizar Ganim (2021)
This research is a quantitive study which aims to determine the effect of price, promotion, and product quality on purchase decision. The sample in this study were 100 reebok's consumer who made the purchases around 2019-2020. The sampling tehnique was done by using probability sampling with simple random sampling. Data collection was carried out using a questionnaire. The analysis technique used in this research is Partial Least Square (PLS) analysis using the SmartPLS 3.0 application. The result of this study are that price didn't have a significant effect on purchase decision, promotion didn't have a significant effect on purchase decision, product quality has a significant effect on purchase decision